Faktor–Faktor Yang Memengaruhi Produktivitas Nanas Di Kabupaten Subang - Dwi Nanda Putri, Dini; Pambudy, Rachmat; Gita Dewi, Triana (Forum Agribisnis, 2024)
Pineapple productivity in Subang Regency has tended to decline in recent years. The resulting pineapple productivity is also still lower than the pineapple productivity target of Subang Regency. To increase pineapple productivity, knowing the factors that affect it is necessary. Therefore, this study analyzes factors influencing pineapple productivity in Subang Regency. The study was conducted at Kumpay and Bunihayu Village Jalan Cagak District with a total sample of 40 farmers. The analytical method used is descriptive analysis and Cobb-Douglass function analysis. The regression results show that only 2 of 6 factors have a significant effect. The number of plants and the use of ZPT significantly positively affected pineapple productivity. The use of these two factors is still not optimal. To increase pineapple productivity, farmers can increase the number of plants and ZPT as recommended.